Influence of bagasse versus rice straw with oil sources in a total mixed ration on feed intake, digestibility and blood chemistry of crossbred Thai Native x American Brahman cattle - Amartsana, I.; Prakobsaeng, N.; Polviset, W. (Diponegoro University, 2020)
This study was aimed to analysis the effects of roughage sources and oil sources in a total mixed ration (TMR) on voluntary feed intake, digestibility and blood chemistry. The study was conducted using four crossbred Thai Native X American Brahman cattle, aged 1.5 years old and with a live weight of 177±34 kg, which were trialled by using a 2x2 factorial in 4×4 Latin square design. All cattle received TMR diets supplemented with bagasse and palm oil, bagasse and sunflower oil, rice straw and palm oil, rice straw and sunflower oil. Each period of feeding lasted for 21 days. During the experimental periods, all cattle were fed ad libitum and with a water supply. The results revealed that roughage sources and oil sources did not affect voluntary feed intake, digestibility and blood chemistry. It was concluded from this experiment that using bagasse or rice straw as the roughage sources with palm oil and sunflower oil mixed in the TMR were suitable for use in beef cattle diets, especially using bagasse with palm oil because of the lowest price (0.28 USD/kg) when compared to the other treatments.